GENETIC FACTORS OF MALE INFERTILITY, THEIR COMBINATIONS AND THE SPERMATOLOGICAL CHARACTERISTICS OF MEN WITH FERTILITY FAILURES - N. Yu. Safina; T. A. Yamandi; V. B. Chernykh; L. V. Akulenko; S. V. Bogolyubov; I. I. Vityazeva; O. P. Ryzhkova; A. A. Stepanova; T. A. Adyan; E. A. Bliznets; A. V. Polyakov (Андрология и генитальная хирургия, 2018)
The objective is to study the occurrence of common genetic factors of male infertility in men with reproductive problems, their combinations and spermatological characteristics.Materials and methods. 393 men with infertility in marriage were examined. According to the results of the cytogenetic study, the sample is divided into 3 groups: 135 men with numerical sex chromosome abnormalities; 58 male patients with a balanced structural rearrangement; 200 men with normal karyotype. Y chromosome microdeletions, CFTR gene mutations and CAG-repeats polymorphism of AR gene were analyzed.Results. The Y-chromosome microdeletions partially AZFc deletions were detected in 13 % male patients with sex chromosome abnormalities. A combination of chromosomal abnormalities with AZF deletions and/or CFTR gene mutations and long CAG repeats of AR gene was found in 19 % infertile men with balanced chromosome rearrangements. Infertile men with normal male karyotype presented the frequency of common genetic factors of male infertility was almost 2 times higher than the combined frequency of these factors in groups of patients with chromosomes abnormalities. Azoospermia in men with normal karyotype and patients with chromosome abnormalities was diagnosed with the same frequency (58 %). In all men who have identified the presence of two or more genetic factors of male infertility, severe forms of pathozoospermia (azoospermia and severe oligozoospermia) were found.Conclusion. The combination of genetic factors of male infertility is accompanied by severe forms of pathozoospermia that indicates a possible additive effect of negative effect on spermatogenesis and male fertility.